أبعاد الهوية الثقافية في الكتب المدرسية للتعليم الابتدائي - لقوقي, الهاشمي; بن زاهي, منصور; بن خيرة, سهيلة (جامعة الوادي - University of Eloued, 2021)
تهدف هذه الدراسة إلى الكشف عن دلالات الهوية الثقافية المتضمنة في كتب المواد الاجتماعية للسنة الثالثة ابتدائي، حيث تحددت مشكلة الدراسة بالسؤال الرئيسي التالي: ما مدى توافر أبعاد الهوية الثقافية في كتب المواد الاجتماعية بمرحلة التعليم الابتدائي في الجزائر؟. ولتحقيق أهداف الدراسة استخدم أسلوب تحليل المحتوى, واتخذت الكلمة كوحدة للتحليل لاستخراج مؤشرات الهوية المتضمنة في الكتب المذكورة, كما تم التأكد من ثبات التحليل من خلال إعادة عملية التحليل. Abstract: This study aims to detect signs of cultural identity contained in the social studies's books of the third year in primary school, where the study identified the main problem by asking the following question: To what extent are the dimensions of cultural identity available in the books of social subjects at the primary education stage in Algeria? To achieve the study's objects used content analysis method, and has taken the word as unit of analysing for the extracting the identity indicators included in the books mentioned, the stability of analysing has been confirmed by re-analysis process.
مقال
Keywords: الهوية الثقافية؛ الكتب المدرسية؛ التعليم الابتدائي; first Cultural identity, school's books, primary education